Social rehabilitation glitch - opinions of convicted men and women on preparation for life outside prison - Bunio-Mroczek, Paulina; Kacprzak, Andrzej (Research on social problems in (pre-)pandemic reality, 2023)
Poland is the country with the largest number of prisoners in the European Union, and their number has been constantly growing again for several years. This tendency takes place despite the widespread questioning of the effectiveness of the social rehabilitation system, which is supported by, for example, high rates of recidivism. The return of former convicts to crime, courts and prisons takes place in the specific context of Polish penitentiary and post-penitentiary studies. After being released, former prisoners experience many difficulties in trying to secure their social and economic resources, which - especially with a deficit of support - often contributes to their repeated criminalization. The text deals with the issues of social rehabilitation and post-penitentiary aid in Poland from the perspective of men and women serving prison sentences. The empirical basis of the analyzes are focused group interviews conducted with recidivists and recidivists serving imprisonment in prisons in Poland.